Pengintegrasian Kecakapan Hidup (Life Skill) dalam Silabus Mata Kuliah Pendidikan Ekonomi - Jusuf Kasrori (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2006)
Curriculum change into competence based education can give implications to the economy course syllabus. The curriculum change should be supported by lectures as a course syllabus developer. The syllabus development aims to give students with relevant life skill for their future. Therefore, life skills should be integrated to syllabus development, so the students can apply the knowledge to their ordinary life. The process can be integrated to the economy education course.